Análisis de la demanda de lácteos en Colombia (2007-2013) (2014)
In the present work an estimate of the price, income and cross-price elasticities of the demand of whole pasteurized milk, whole UHT milk and peasant and double cream cheeses is made in Colombia for the period between 2007 and 2013. The starting point is to justify the why the work is carried out, taking into account the participation of the dairy sector in the livestock and national GDP, generation of employment, increasing behavior of the consumption of dairy products, among other macroeconomic variables; besides taking into account the differentiated behavior of each department regarding the consumption of dairy products.